NEW POSSIBILITIES OF ATROPHIC CHANGES PREDICTING IN VAGINAL TISSUE AT WOMEN IN POST REPRODUCTIVE PERIOD - O. G. Sarkisan (Кубанский научный медицинский вестник)
With the aim of increasing the effectiveness of early diagnostics and medical therapy of atrophic colpitis the valuation analysis of the kallikrein-kinin system and the activity of inducible NO-synthase in peripheral blood is carried out. 35 women (mean age 51±2.8 years) with moderate atrophy of the vagina was examined. A comparison group - 35 women (mean age 48 ± 3.6 years) without signs of atrophy and urogenital symptoms. The results of the study showed that in the serum of blood of women with symptoms of atrophic colpitis marked increase in the activity of kallikrein, decrease of prekallikrein level, inhibition of the inhibitory activity of α2-macroglobulin and recorded a sharp increase in the activity of inducible NO-synthase in clinical group of women that reflects the body's response on local disruption of the microcirculation. The results analysis testify about possibility of microcirculation local disturbances before clinical manifestations of the disease, that allow to diagnose of tissue degenerative changes in the shortest time with the use of additional laboratory method in the absence of clear clinical signs of the disease.